Producing Work Ready Graduates Through Islamic Education Management Strategies - Balu, Hidayanti; Na'imah, Na'imah; Rizqa, Dewi; Khoirunnisa, Mila (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
The policy regarding the need to produce graduates with high job readiness encourages Islamic Education Management study programs to be cautious in applying the correct strategies. Therefore, this article aims to concretely identify the strategies that can be used by Islamic Education Management programs to produce job ready graduates, explain why using these strategies correctly is important, and discuss the implications of the strategies employed in Islamic Education Management. This research was conducted using a qualitative method with a literature review approach. The researcher applied content analysis as a technique for data analysis. The results of this study indicate that the implementation of management strategies for Islamic education has shown good results in producing graduates who are job ready. This is evident from the high job readiness of graduates who successfully secured employment in relevant fields and institutions within a relatively short period, Based on the findings, the strategies employed by Islamic Education Management in producing job ready graduates include coaching, development, improvement, and training. The existence of these strategies serves to produce competent, competitive, quality and character driven graduates. The implications of the strategies applied in Islamic Education Management include the creation of managerial knowledge competencies among graduates, high job absorption rates, competent graduates, and graduates excelling in various professions related to Islamic Education Management. This research can contribute to the development of effective learning models that can enhance graduates adaptation in the workforce.